Optimizing high-order harmonic generation with two-color fields, polarization gating, and static electric fields - Duke Onsure Nyangau; Kebwaro Jeremiah Monari; Rurimo Kihara; Njoroge Stephen Maina (Universitas Sebelas Maret, 2025)
The optimization of high order harmonic generation process under the combination of a plasmonic enhanced two color field with modulated polarization gating and a static electric field was investigated in this study. Through investigating the harmonic spectrum yields by numerical solution of the one-dimensional time dependent Schrödinger equation, it is shown that the inhomogeneity of the local fields, polarization angle, confinement of the electron movement through the use of two color and static electric fields plays an important role in the HHG process. It is further observed that when the three schemes are used together a high harmonic yield, broadened harmonic plateau and a significantly increased harmonic cutoff point up to 600th order are obtained confirming an improved harmonic conversion efficiency.